Meet and Greet for new international students enhances community bonds at UMPSA - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2024)
PEKAN, 27 February 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised a Meet and Greet programme for new international students to welcome new arrivals to the campus.